Proposta de modelo de desenvolvimento socioambiental para municípios de pequeno porte a partir do gerenciamento integrado dos resíduos sólidos urbanos (GIRSUs): um estudo teórico-empírico - Guelbert, Tanatiana Ferreira (2008)
This study proposes a theoretical model of Socio-environmental Development for Small Cities upon Integrated Management of Urban Solid Waste (IMUSWs), as a matter to promote social inclusion, generation of employment and income, and improvement of life quality of people who work in collecting recyclable materials, namely “catadores” and “catadoras”. The model was inspired in the principles that guide a house construction and the Toyota Production System. Considering that for the roof or top of the house, which goal is Sustainable Development, requires a solid foundation, defined in this work as variables: Awareness, Environmental Education and Selective Collection. Between the roof and the foundation are the pillars comprised by the variables: Cooperative, Training, Vocational School, Crafts, Landfill, Composting and Energy that will support to achieve the goals which are at the top: Income Generation, Life Quality and Socio-environmental Responsibility. Besides the above issues also have been explored the Management of Urban Solid Waste (USWs), Projects of Clean Development Mechanisms (CDM) and Market of Carbon Credit (MCC), all focused on urban waste in small towns. The shortness of literature about Integrated Management of USWs of CDM and MCC for small cities in Brazil makes the research significant and timely. In order to contribute to developing the model a case study was conducted in a small city. To collect the data a questionnaire, available in the Integrated Management Manual, was used and also semi-structured interviews, according to a methodology proposed by the Cooperative COSELIX with representatives of Catadores and the Department of Environment, information available in official documents and technical visits. As a result, the study showed a lack of commitment, material, human and financial resources of small cities to promote IMUSWs, and the importance of integration by the City Hall, in the implementation and deployment of programs, strategies and/or tools addressed this work seeing the Socio-environmental Development as concepts evidenced in the model proposed by this project.